1) tìm x
a) 11.(x-6)=4x+11
b) |x-3|+1=x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: x=-5/11+2/11=-3/11
b: =>x=-3/24+20/24+1/24=18/24=3/4
c: =>5/8-x=1/9+5/4=4/36+45/36=49/36
=>x=5/8-49/36=-53/72
d: =>2/3-x=1/3
=>x=1/3
e: =>1/5:x=12/35
=>x=7/12
\(A=\left(4x^2+4x+1\right)+10=\left(2x+1\right)^2+10\ge10\)
\(A_{min}=10\) khi \(2x+1=0\Rightarrow x=-\dfrac{1}{2}\)
\(B=\left(x-1\right)\left(x+6\right)\left(x+2\right)\left(x+3\right)=\left(x^2+5x-6\right)\left(x^2+5x+6\right)=\left(x^2+5x\right)^2-36\ge-36\)
\(B_{min}=-36\) khi \(x^2+5x=0\Rightarrow\left[{}\begin{matrix}x=0\\x=-5\end{matrix}\right.\)
\(C=\left(x^2-2x+1\right)+\left(y^2-4x+4\right)+2=\left(x-1\right)^2+\left(y-2\right)^2+2\ge2\)
\(C_{min}=2\) khi \(\left(x;y\right)=\left(1;2\right)\)
a: ta có: \(\left(x+3\right)\left(x-1\right)-x\left(x-5\right)=11\)
\(\Leftrightarrow x^2+2x-3-x^2+5x=11\)
\(\Leftrightarrow x=2\)
b: Ta có: \(\left(x+4\right)\left(x^2-4x+16\right)-x\left(x+1\right)\left(x+2\right)+3x^2=0\)
\(\Leftrightarrow x^3+64-x^3-3x^2-2x+3x^2=0\)
\(\Leftrightarrow2x=64\)
hay x=32
a) \(\left(2x-1\right)^2-25=0\)
⇔ \(\left(2x-1\right)^2-5^2=0\)
⇔ \(\left(2x-1-5\right)\left(2x-1+5\right)=0\)
⇒ \(2x-1-5=0\) hoặc \(2x-1+5=0\)
⇔ \(x=3\) hoặc \(x=-2\)
Bài 1: Tìm x
a) (2x-1) ² - 25 = 0
<=> (2x-1)2 = 25
<=> 2x-1 = 5 hay 2x-1 =-5
<=> 2x= 6 hay 2x=-4
<=> x=3 hay x= -2
Vậy S={3; -2}
b) 3x (x-1) + x - 1 = 0
<=> (x-1)(3x+1)=0
<=> x-1=0 hay 3x+1=0
<=> x=1 hay 3x=-1
<=> x=1 hay x=\(\dfrac{-1}{3}\)
Vậy S={1;\(\dfrac{-1}{3}\)}
c) 2(x+3) - x ² - 3x = 0
<=> 2(x+3)- x(x+3)=0
<=> (x+3)(2-x)=0
<=> x+3=0 hay 2-x=0
<=> x=-3 hay x=2
Vậy S={-3;2}
d) x(x - 2) + 3x - 6 = 0
<=> x(x-2)+3(x-2)=0
<=> (x-2)(x+3)=0
<=> x-2=0 hay x+3=0
<=> x=2 hay x=-3
Vậy S={2;-3}
e) 4x ² - 4x +1 = 0
<=> (2x-1)2=0
<=> 2x-1=0
<=> 2x=1
<=> x=\(\dfrac{1}{2}\)
Vậy S={\(\dfrac{1}{2}\)}
f) x +5x2 = 0
<=> x(1+5x)=0
<=>x=0 hay 1+5x=0
<=> x=0 hay 5x=-1
<=> x=0 hay x= \(\dfrac{-1}{5}\)
Vậy S={0;\(\dfrac{-1}{5}\)}
g) x ²+ 2x -3 = 0
<=> x2-x+3x-3=0
<=> x(x-1)+3(x-1)=0
<=> (x-1)(x+3)=0
<=> x-1=0 hay x+3=0
<=> x=1 hay x=-3
Vậy S={1;-3}
a: \(\Leftrightarrow-x^2-3x+x+3+x^2-6x=11\)
=>-8x+3=11
=>-8x=8
hay x=-1
b: \(\Leftrightarrow3x^2-15x+x-5-3x^2+3x=5\)
=>-11x=10
hay x=-10/11
Bài 2:
a: 4x(x-3)+6(3-x)=0
=>4x(x-3)-6(x-3)=0
=>(x-3)(4x-6)=0
=>\(\left[{}\begin{matrix}x-3=0\\4x-6=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=3\\x=\dfrac{3}{2}\end{matrix}\right.\)
b: \(x^3-x\left(x+1\right)\left(x-1\right)=14\)
=>\(x^3-x\left(x^2-1\right)=14\)
=>\(x^3-x^3+x=14\)
=>x=14
c: \(\left(x^2-x\right)^2+2\left(x^2-x\right)=8\)
=>\(\left(x^2-x\right)^2+2\left(x^2-x\right)-8=0\)
=>\(\left(x^2-x\right)^2+4\left(x^2-x\right)-2\left(x^2-x\right)-8=0\)
=>\(\left(x^2-x\right)\left(x^2-x+4\right)-2\left(x^2-x+4\right)=0\)
=>\(\left(x^2-x+4\right)\left(x^2-x-2\right)=0\)
=>\(\left(x^2-2\cdot x\cdot\dfrac{1}{2}+\dfrac{1}{4}+\dfrac{15}{4}\right)\left(x-2\right)\left(x+1\right)=0\)
=>\(\left(x-2\right)\left(x+1\right)=0\)
=>\(\left[{}\begin{matrix}x-2=0\\x+1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-1\end{matrix}\right.\)
a) 3x(4x-3)-2x(5-6x)=0
\(\Leftrightarrow12x^2-9x-10x+12x^2=0\)
\(\Leftrightarrow24x^2-19x=0\)
\(\Leftrightarrow x\left(24x-19\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\24x-19=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\24x=19\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=\dfrac{19}{24}\end{matrix}\right.\)
Vậy x=0 hoặc x=\(\dfrac{19}{24}\)
Lời giải:
a.
$\frac{2}{3}+\frac{1}{3}:3\times x=20\text{%}$
$\frac{2}{3}+\frac{1}{9}\times x=\frac{1}{5}$
$\frac{1}{9}\times x=\frac{1}{5}-\frac{2}{3}=\frac{-7}{15}$
$x=\frac{-7}{15}: \frac{1}{9}=\frac{-21}{5}$
b.
$\frac{3-x}{5-x}=\frac{6}{11}$
$\Rightarrow 6(5-x)=11(3-x)$
$\Rightarrow 30-6x=33-11x$
$\Rightarrow 5x=3$
$\Rightarrow x=\frac{3}{5}$
a)11(x-6)=4x+11
11x - 11*6=4x+11
11x-4x=11+11*6
7x=77
x=77/7
x=11
b)lx-3l+1=x
lx-3l=x-1
\(\Rightarrow x-3\in\left\{-\left(x-1\right);x-1\right\}\)
Ta có:
TH1:x-3=-(x-1)
x-3=-x+1
x-(-x)=1+3
2x=4
x=4/2
x=2
TH2:x-3=x-1
x-x=3-1
0=2
\(x\in rỗng\)
Vậy x=2